Human adenovirus type 1 related to feline adenovirus: Evidence of interspecies transmission - Phan T.G. (2014)
Adenovirus is recognized to be a significant global enteropathogen in association with sporadic cases as well as outbreaks of acute gastroenteritis in humans. Based on the genetic analysis, one adenovirus strain bearing feline adenovirus gene was detected in a fecal specimen collected from a 1-year old female child with acute gastroenteritis in Japan. The human adenovirus detected and feline adenovirus shared high identities (100% and 97%) at the amino acid levels of hexon and fiber genes, respectively, and they belonged to the same human Ad1 cluster (known as the prototype Adenoid 71). These findings suggest that the interspecies transmission of adenovirus between humans and felines might occur in nature. This report is noteworthy because it is the first, to the best of our knowledge, providing evidence of adenovirus type 1 transmission between humans and animals, and highlights possible zoonoses in humans. Further epidemiological studies should be conducted to determine whether this adenovirus strain will be emergent in future.